Unveiling multidimensional poverty: Insights from the EU - Robayo-Abril, Monica (2025)
The European Union has improved living standards, yet welfare disparities persist across regions, countries, and demographic groups. This paper uses data from European Union Statistics on Income and Living Conditions cross-sectional and longitudinal surveys and the at-risk-of-poverty or social exclusion framework to analyze recent temporal trends in absolute multidimensional poverty across the 27 countries in the European Union and its subregions. The analysis quantifies the extent, composition, and factors associated with the higher risks of multidimensional poverty across four countries (Bulgaria, Romania, Croatia, and Poland) and extends the at-risk-of-poverty or social exclusion framework to consider other dimensions of deprivations. The paper analyzes the extent of multidimensional poverty among the Roma population in Bulgaria and assesses the extent of chronic income poverty and chronic material deprivation among this group. The analysis reveals that some European Union member states present strikingly divergent trends in multidimensional poverty compared to the European Union average, and there have been different rates of progress across subregions. Results of the analysis of the four countries of interest indicate that although monetary poverty risks are comparable across these countries, there are notable variations in the incidence of nonmonetary indicators and the intensity of deprivations. However, the likelihood of being multidimensionally poor is conditioned by similar individual, socioeconomic, and family characteristics across countries. The Roma population in Bulgaria encounters more concurrent disadvantages compared to the broader population and is significantly more likely to be disproportionately represented among those experiencing chronic poverty and material deprivations. These findings underscore the urgent need for targeted policy interventions that tackle the most pressing needs of disadvantaged populations. Finally, the study proposes a set of potential policy interventions to address structural inequalities and improve the well-being of vulnerable populations.